Molecular and antigenic evolution and geographical spread of H5N1 highly pathogenic avian influenza viruses in western Africa. - (:unkn) unknown (My University, 2007)
In Africa, highly pathogenic avian influenza H5N1 virus was first detected in northern Nigeria and later also in other regions of the country. Since then, seven other African countries have reported H5N1 infections. This study reports a comparison of full-length genomic sequences of H5N1 isolates from seven chicken farms in Nigeria and chicken and hooded vultures in Burkina Faso with earlier H5N1 outbreaks worldwide. In addition, the antigenicity of Nigerian H5N1 isolates was compared with earlier strains. All African strains clustered within three sublineages denominated A (south-west Nigeria, Niger), B (south-west Nigeria, Egypt, Djibouti) and C (northern Nigeria, Burkina Faso, Sudan, Côte d'Ivoire), with distinct nucleotide and amino acid signatures and distinct geographical distributions within Africa. Probable non-African ancestors within the west Asian/Russian/European lineage distinct from the south-east Asian lineages were identified for each sublineage. All reported human cases in Africa were caused by sublineage B. Substitution rates were calculated on the basis of sequences from 11 strains from a single farm in south-west Nigeria. As H5N1 emerged essentially at the same time in the north and south-west of Nigeria, the substitution rates confirmed that the virus probably did not spread from the north to the south, given the observed sequence diversity, but that it entered the country via three independent introductions. The strains from Burkina Faso seemed to originate from northern Nigeria. At least two of the sublineages also circulated in Europe in 2006 as seen in Germany, further suggesting that the sublineages had already emerged outside of Africa and seemed to have followed the east African/west Asian and Black Sea/Mediterranean flyways of migratory birds.
Keywords: African Research